Exploration of treatment strategies for cerebral cavernous malformations: two case reports on non-resection treatment and literature review - Han, Yibo; Liang, Dong; Guo, Jing; Wang, Yibao; Wang, Yong (Frontiers in Oncology, 2025)
BackgroundCavernous malformations are common vascular abnormalities of the central nervous system, but cavernous malformations of the cerebral aqueduct are rare. The choice of treatment is influenced by various factors.Case DescriptionWe report two cases of midbrain cavernous malformations. Both cases involved midbrain lesions obstructing the cerebral aqueduct, leading to obstructive hydrocephalus. The primary symptoms and complaints of the patients were related to hydrocephalus. Prior to surgery, patients underwent comprehensive imaging evaluations and received endoscopic third ventriculostomy rather than tumor resection. Both patients had favorable recoveries. We also reviewed the literature and discussed the choice of treatment strategies.ConclusionCavernous malformations are slow-progressing central nervous system lesions with a relatively benign natural course. When selecting a treatment strategy, clinicians should carefully consider the underlying cause of the patient’s primary symptoms and the specific objectives of the surgery. Avoiding overly aggressive resection that fails to address the main symptoms and potentially causes irreversible damage is crucial.